Rodents and herpetofauna as household pests in the Accra Metropolis, Ghana - Attuquayefio, D.K.; Gbogbo, F.; Krobea-Asante, A. (West African Journal of Applied Ecology (11): 197-208, 2008)
Small manuals and herpetofaunal household pests, known for their economic damages, health implication and nuisance effects on people, are frequently seen in the Ghanaian home environment. This study, therefore, was aimed at assessing the relationship between the level of infrastructural development and the abundance, control methods and perception of people about rodents and herpetofaunal household pests. The results indicated that the incidence of rodents and anurans decreased with increasing infrastructural development on of the areas. The use of control measures as well as the type of control measure employed was also dependent on infrastructural development with the underdeveloped areas employing more physical and sanitary measures on daily basis, contrary to weekly and monthly bases in the developed and developing areas. The chemical control was mostly used in the developing areas while biological control as the main vertebrate pest control method in the developed area. The level of infrastructural development of an area, therefore, gives an indication of the kind of herpetofaunal and small mammal pests likely to be prevent in an area, and the consequence of their infestation. This information is particularly important to the choice of accommodation for rental purposes as well as town or planning.
Keywords: Rodents; Herpetofauna; Pests; Accra Metropolis